Knowledge to be Taught of Computational Thinking: A Praxeological Analysis - Fathimah, Nusuki Syari'ati; Arianti, Andini Setya; Junaeti, Enjun (FKIP Universitas Lampung, 2024)
Efforts to enhance the quality of informatics education at the secondary school level within the Merdeka Curriculum focus on identifying learning barriers. This study analyzes secondary school informatics textbooks to identify potential learning obstacles through praxeological analysis. The analysis focuses on tasks, techniques, technologies, and theories employed in the textbooks to determine whether the construction of students' knowledge is epistemically aligned. Based on the praxeological analysis, 20 tasks were identified, categorized into five task types. The techniques used to solve these tasks are aligned with computational thinking skills. Four reference theories are consistent with the data and algorithm analysis elements integrated with computational thinking elements in the latest curriculum: algorithms, data representation, data structures, and optimization. This study identifies several potential learning barriers: ontogenic obstacles arise from the sequencing of task types, epistemological obstacles from the pre-existing conceptual frameworks, and didactic obstacles from the clarity of instructions and task complexity. In conclusion, this study recommends improvements to the reference epistemological model, particularly in adjusting instructions and the sequencing of tasks. Keywords: praxeology, knowledge to be taught, informatics, learning obstacle, computational thinking. DOI: http://dx.doi.org/10.23960/jpmipa/v25i4.pp1752-1770